À Elbeuf les paysages urbains racontent l’histoire de la ville - Confins (Confins)
The town of Elbeuf, in Normandy, was once famous for its drapery industry (manufacture of woollen fabrics), which has now disappeared, but it is now renowned for the conservation and enhancement of its rich industrial heritage and one of its remarkable features is that its urban landscapes clearly show the different phases in the town's history